Eco-friendly synthesis of zinc oxide nanoparticle using Centella asiatica: phytochemical analysis, characterization and antimicrobial activity assessment - Poudel, Bhoj Raj; Tiwari, Laxmi; Magar, Chunu; Dhungana, Sujan; Poudel, Aayush Raj; Khadka, Devendra; Pokhrel, Megh Raj; Baral, Janaki (Scientific World, 2025)
Zinc oxide nanoparticles (ZnO NPs) were synthesized using an eco-friendly approach, utilizing the aqueous extracts of Centella asiatica (C. asiatica), a perennial herbaceous plant with important therapeutic uses, locally called 'Ghodtapre' in Nepali. In this work, plant extracts from C. asiatica were used to produce ZnO NPs in an environmentally friendly manner. ZnO NPs were characterized through X-ray diffraction (XRD), UV-visible spectroscopy, and Fourier transform infrared (FTIR) spectroscopy. A noticeable absorption peak at 375 nm, which agrees with a band gap of 2.80 eV, was determined by UV analysis. The FTIR analysis confirmed the existence of functional groups that serve as capping and stabilizing agents. XRD analysis estimated 11.74 nm of the crystallite size of the ZnO NPs. According to phytochemical studies, flavonoids, tannins, quinine, terpenoids, and alkaloids are all present. Antimicrobial testing confirms the nanoparticles' effectiveness against both bacteria and fungi.